Reproductive characteristic of the female laboratory rat - Hamid, Huda Yahia; Abu Bakar @ Zakaria, Md Zuki (Academic Journals, 2013)
The laboratory rat is widely used in research studies as a model of mammalian health and disease. This review provides the basic facts about female rat reproduction and highlights the reproductive characteristics which make the rat a preferred animal model for research on reproduction. Rats have short estrous cycle, lasting four to five days. The estrous cycle consists of four stages known as proestrus, estrus, metestrus and diestrus. Phases of the estrous cycle can be detected by observing behavioral changes or examining vaginal cytology. Detection of sperm in vaginal smear is an excellent predictor of pregnancy in rats. Implantation is initiated on day 5 and completed by day 7 of pregnancy. Gestation takes 21 to 23 days from copulation to parturition. Short estrous cycle and gestation period make the rat an ideal animal model for research on reproduction.